LEARNING ASSISTANCE FOR STUDENTS IN SOLVING CONTEXTUALLY BASED QUESTIONS: PENDAMPINGAN BELAJAR PESERTA DIDIK DALAM MENYELESAIKAN SOAL BERBASIS KONTEKSTUAL - Nur, Fitriani; Ramadani, Nurul Fitrah; Sulasteri, Sri; Majid, Ahmad Farham; Andi Mattoliang, Lisnasari (Khidmatuna: Jurnal Pengabdian Masyarakat, 2024)
Mathematical problem solving ability is an essential skill that allows students to apply mathematical concepts to problems. However, there are still quite serious problems related to students' low mathematical problem solving abilities. Therefore, service in the form of assistance in solving contextual-based questions on SPLDV material aims to facilitate students' mathematical problem solving abilities. This assistance is provided to class VIII MTsN Gowa students. Evaluation of the level of success of service is carried out through learning outcomes tests which include contextual-based questions and student response questionnaires. Based on the analysis of learning outcomes tests, it was found that students' mathematical problem solving abilities still need to be trained. However, based on analysis of student response questionnaires, a positive response was obtained regarding the implementation of mentoring. Thus, service activities in the form of assistance in solving contextual-based problems are feasible to be carried out on an ongoing basis in an effort to improve students' mathematical problem solving abilities.